Plant and Pest Diagnosis and Identification through DDIS - Jiannong Xin; Lyle J. Buss; Carrie Lapaire Harmon; Pete Vergot; Marc S. Frank; William J. Lester (EDIS)
Pest identification and diagnosis can be difficult and often require consultation with a specialist. Extension county faculty, state specialists, and faculty of the UF/IFAS Office of Information Technology developed the Distance Diagnostic and Identification System (DDIS), which allows users to submit digital images obtained in the field or after delivery to a local Extension office for rapid diagnosis and identification of pest insects, weeds, diseases, and animals. This 4-page document discusses typical DDIS hardware and camera, the DDIS process, sample types, user roles, DDIS for Extension clientele, and DDIS Mobile. Written by J. Xin, L. Buss, C. Harmon, P. Vergot III, M. Frank, and W. Lester, and published by the UF/IFAS Department of Agricultural and Biological Engineering, revised March 2018. http://edis.ifas.ufl.edu/ae225